Aspergillus niger pneumonia as superinfection in a patient with pulmonary tuberculosis - Ewig, Santiago; Gatermann, Sören; Phillipou, Stathis; Giesa, Christian; Hecker, Erich (Pneumologie, 2023)
We report a patient with severe cavitary pulmonary tuberculosis and Aspergillus niger superinfection, whose only comorbidity was untreated diabetes mellitus. A. niger pneumonia was proven by PCR, sequencing and culture of pleural and respiratory secretions. The patient was successfully treated with a four-drug antituberculous regimen, liposomal amphotericin B (up to 5 mg/kg/d) and pleuro-pneumonectomy. Histology of the resected lung revealed destroyed lung tissue with inflammatory cells and fungal conidia. There were large deposits of polarising material, which was found to be calcium oxalate. There was also nodular caseating necrosis bordered by epitheloid cells and connective tissue. Thus, all diagnostic criteria for invasive A. niger infection were met. Several local risk factors, such as extensive lung damage and tissue acidification, may have favoured superinfection by A. niger. This case highlights the diagnostic value of calcium oxalate crystals in lung tissue and the need for combined antimicrobial and surgical treatment in extensive invasive aspergillosis caused by A. niger.